Tiefenverteilung benthischer Foraminiferen am portugiesischen Kontinentalhang - Seiler, Wolfgang Christoph (Bornträger, 1975)
Living and dead benthic Foraminifera of 26 sediment surface samples from the East Atlantic continental margin (off Portugal) are studied. The stations are located on two profiles off Cape Mondego and off Cape Sines, ranging in water depth from 45 to 3905 meters. The highest values of standing crop are on the shelf (200 m) (up to 420 specimens/10 cm3). Below 1000 m watet depth standing crop is low (5-24 specimens/10 cm3). 151 species and species groups are distinguished; 41 species are described and partly illustrated. The Figures 13-18 show the relative frequencies and the depth distributions (living and dead) of the most important species. Most of the living species do occur in a wide depth range. Faunal depth boundaries are at 50/100 m, at 600/800 m, and at 1000 m (Fig. 19). Results published from the North Atlantic and the East Mediterranean do not differ from those obtained in samples off Portugal. The Mediterranean outflow probably does not influence the benthic foraminiferal fauna off Portugal. Depth of water (e. g. hydrostatic pressure) or another factor being controlled by depth (e. g. limitation of food supply) seems to be the most important factor of the benthic foraminiferal distribution.